2014
DOI: 10.1016/j.brainres.2014.05.049
|View full text |Cite
|
Sign up to set email alerts
|

TLR signaling controls lethal encephalitis in WNV-infected brain

Abstract: Toll-like receptors (TLRs) are known to be activated in Central Nervous System (CNS) viral infections and are recognized to be a critical component in innate immunity. Several reports state a role for particular TLRs in various CNS viral infections. However, excessive TLR activation was previously reported by us in correlation with a pathogenic, rather than a protective, outcome, in a model of SIV encephalitis. Here we aimed at understanding the impact of TLR-mediated pathways by evaluating the early course of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 44 publications
4
24
0
Order By: Relevance
“…In microglia, there are constitutively expression of TLR3, TLR7 and TLR9 [12]. Although the basal level of these membrane protein is relatively low, their expression is strongly upregulated after viral infection [39,45].…”
Section: Toll Like Receptors In Microglia Mediated Neuroinflammationmentioning
confidence: 99%
“…In microglia, there are constitutively expression of TLR3, TLR7 and TLR9 [12]. Although the basal level of these membrane protein is relatively low, their expression is strongly upregulated after viral infection [39,45].…”
Section: Toll Like Receptors In Microglia Mediated Neuroinflammationmentioning
confidence: 99%
“…encephalitis upon TBEV infection(59). In contrast, mouse studies with other Flaviviruses such as WNV and ZIKV revealed a protective role of TLR-signaling(60,61).Taken together, upon in vitro TBEV infection of mouse-derived brain resident cell subsets, astrocytes are the main IFN-β producers. Early after infection, astrocytes are stimulated in a MAVS-dependent manner, presumably via RLR signaling, whereas at later time points MyD88/TRIF-signaling was needed.…”
mentioning
confidence: 99%
“…Alternatively, a systemic inflammatory response may be induced by early haematogenous circulation of virus (viraemia), stimulating viral sensors, such as Toll-like receptors, at the blood-tissue interphase [327][328][329].…”
Section: Discussionmentioning
confidence: 99%